2018
DOI: 10.29226/tr1001.2018.22
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation Of The Impact Of Exchange Rate Fluctuations On The Performance Of Selected Listed Firms In Nigeria

Abstract: This study investigated the impact of exchange rate fluctuations on firm's performance in Nigeria. Having noted the impact of exchange rate fluctuation from the literatures, it become paramount to investigate the impact in the Nigeria context. In this study, seven research questions were formulated which led to the test of seven hypotheses. The major objective of the study was to empirically investigate the impact of exchange rate fluctuations on return of investment. The study makes use of descriptive and ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…(Hyo, 2018) produced a finding that a group of companies that were positively affected by NT appreciation experienced a rise in NP in the short term, but there were a group of companies that were negatively affected due to ER appreciation, apparently experiencing an increase in the CV in the medium and long term. (Lee, 2017) indicated that produces findings that ER appreciation does not cause a decrease in the level of investment, while (Williams, 2018) stated that there is a positive relationship between ER and ROI, while (Nagahisarchoghani et all., 2018) stated there is a weak relationship between ER and prices per book stock/ per market price, however (Okika et all., 2018) makes finding that NT has no significant effect on company profitability.…”
Section: Inflation Rate (It)mentioning
confidence: 99%
See 1 more Smart Citation
“…(Hyo, 2018) produced a finding that a group of companies that were positively affected by NT appreciation experienced a rise in NP in the short term, but there were a group of companies that were negatively affected due to ER appreciation, apparently experiencing an increase in the CV in the medium and long term. (Lee, 2017) indicated that produces findings that ER appreciation does not cause a decrease in the level of investment, while (Williams, 2018) stated that there is a positive relationship between ER and ROI, while (Nagahisarchoghani et all., 2018) stated there is a weak relationship between ER and prices per book stock/ per market price, however (Okika et all., 2018) makes finding that NT has no significant effect on company profitability.…”
Section: Inflation Rate (It)mentioning
confidence: 99%
“…(Hyo Sang, 2018) explained that the effect of ER on positive or negative company performance depends on its involvement in import-export activities at the macro level and industry and company level analysis. Studies with the result that ER has a significant effect on CV were found in (Lee, 2017), (Williams, 2018), (Nagahisarchoghani et all., 2018), (Hyo Sang, 2018) and (Karakus and Bozkurt, 2017).…”
Section: Inflation Rate (It)mentioning
confidence: 99%
“…In the research study, it was concluded that the exchange rate volatility over the period 2004-2013 caused a negative impact on all three variables and adversely affected the performances of companies in Nigeria. Williams (2018) investigated the impacts of the change in exchange rates on the financial performances of companies in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the work of Williams, (2018), he investigated the impact of exchange rate fluctuations on firm's performance in Nigeria. Having noted the impact of exchange rate fluctuation from the literatures, it became paramount to investigate the impact in the Nigeria context.…”
Section: Review Of Empirical Frameworkmentioning
confidence: 99%